Tacrolimus versus cyclosporine a combined with post-transplantation cyclophosphamide for AML In first complete remission: a study from the acute leukemia working party (EBMT) - Bug, Gesine; Labopin, Myriam; Kulagin, Alexander; Blaise, Didier; Raiola, Anna Maria; Vydra, Jan; Sica, Simona; Kwon, Mi; López-Corral, Lucía; Bramanti, Stefania; von dem Borne, Peter; Itälä-Remes, Maija; et al. (Bone marrow transplantation, 2024)
Choice of calcineurin inhibitor may impact the outcome of patients undergoing T-cell replete hematopoietic cell transplantation (HCT) with post-transplant cyclophosphamide (PT-Cy) and mycophenolate mofetil (MMF) for prophylaxis of graft-versus-host disease (GVHD). We retrospectively analyzed 2427 patients with acute myeloid leukemia (AML) in first remission transplanted from a haploidentical (n = 1844) or unrelated donor (UD, n = 583) using cyclosporine A (CSA, 63%) or tacrolimus (TAC, 37%) and PT-Cy/MMF. In univariate analysis, CSA and TAC groups did not differ in 2-year leukemia-free or overall survival, cumulative incidence (CI) of relapse or non-relapse mortality. CI of severe grade III-IV acute GVHD was lower with TAC (6.6% vs. 9.1%, p = 0.02), without difference in grade II-IV acute GVHD or grade III-IV acute GVHD/severe chronic GVHD, relapse-free survival (GRFS). In multivariate analysis, TAC was associated with a lower risk of severe grade III-IV acute GVHD solely with haploidentical donors (HR 0.64 [95% CI, 0.42-0.98], p = 0.04), but not UD (HR 0.49 [95% CI, 0.2-1.21], p = 0.12). There was no significant difference for chronic GVHD. In conclusion, PT-Cy/MMF-based GVHD prophylaxis resulted in favorable OS and GRFS, irrespective of the CNI added. In haploidentical HCT, TAC seemed to prevent severe acute GVHD more effectively than CSA without impact on other outcome parameters.
Keywords: dospělí; Cyclophosphamide; takrolimus; Female; dítě; předškolní dítě; Tacrolimus; Adult; mladý dospělý; ženské pohlaví; Adolescent; lidé; Hematopoietic Stem Cell Transplantation; transplantace hematopoetických kmenových buněk; Immunosuppressive Agents; cyklosporin; Middle Aged; Graft vs Host Disease; retrospektivní studie; Remission Induction; Male; Aged; indukce remise; Young Adult; Child, Preschool; nemoc štěpu proti hostiteli; akutní myeloidní leukemie; Cyclosporine; lidé středního věku; Child; senioři; mužské pohlaví; Retrospective Studies; cyklofosfamid; mladiství; Leukemia, Myeloid, Acute; imunosupresiva; Humans